UK POLICY COMMUNITY VIEWING ETHNIC DIVERSITY POLICY: FROM STRONGER TO WEAKER MULTI-CULTURALISM? - Gooby, Peter Taylor (SCAD Independent, 2015)
Multiculturalism as the dominant approach to managing diversity in the UK has been called into question by politicians, community leaders and academics in recent years. This paper reports interviews about multiculturalism, social cohesion and future policy directions with leading figures in the debate, including Home Affairs Select Committee members, authors of major reports, experts, researchers and academics. The attitudes expressed when discussing overall policy directions do not fit the traditional left-centre-right dimension of British politics but, in most cases, indicate unease at assumed segregate effects of current policy. However, when specific issues (sharia law, faith schooling, dress/ diet codes, political representation) are considered the viewpoints of most interviewees are more pragmatic. Relatively few advocate strong policies to impose British values or move decisively away from a general multiculturalism stance. The transition most widely supported would be from stronger to weaker multiculturalism rather than from multiculturalism to a different approach to diversity.